Clinical differential analysis of severe complications thrombotic microangiopathy and acute graft-versus-host disease following allogeneic hematopoietic stem cell transplantation - Wang, Yuan-yuan; Li, Gang-ping; Fu, Shu-zhen; Fu, Yue-wen; Shen, Yong; Xu, Qing-xia (Frontiers in Oncology, 2025)
BackgroundIdentifying the early markers of transplant-associated thrombotic microangiopathy (TA-TMA) and mild or severe acute graft-versus-host disease poses a significant challenge in the differential diagnosis of severe complications after allo-hematopoietic stem cell transplantation (allo-HSCT).MethodsWe conducted an analysis of 109 patients who developed TA-TMA, grade I-II aGVHD , and grade III-IV aGVHD following allo-HSCTs at our center between 2019 and 2024. Clinical features, laboratory data and outcomes were compared among these groups.ResultsThe median diagnostic time for TA-TMA was 94 days post-transplant, with median survival of 1 month for TA-TMA and 2 months for grade III-IV aGVHD, significantly shorter than 5 months for grade I-II aGVHD. Survival curves for TA-TMA and grade III-IV aGVHD were poorer. Risk factors (RFs) for TA-TMA included fragmented red blood cell proportion, elevated LDH, and renal injury, with hemoglobin showing a protective effect. Cox analysis identified hypertension, cardiac insufficiency, renal injury, fragmented red blood cells, LDH, platelet counts, hemoglobin, and albumin as significant mortality factors for TA-TMA. For grade III-IV aGVHD, hypertension, renal injury, fragmented red blood cells, LDH, TBIL, platelet counts, hemoglobin, and albumin were significant. Multivariate analysis showed that fragmented red blood cells, elevated LDH, and renal injury predicted higher mortality for TA-TMA, while higher platelet counts and albumin levels predicted lower mortality. No independent prognostic factors were found for grade III-IV aGVHD.ConclusionOur analysis highlights the significant challenge of late diagnosis and high mortality in TA-TMA following allo-HSCT. It further identifies a panel of accessible clinical indicators that can aid in early risk assessment and prognostication.